Perbandingan Struktur Bahasa Indonesia dan Bahasa Inggris dalam Perspektif Linguistik Terapan - Achmad Husaini Ibrahim (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This study explores the structural differences between Indonesian and English within the framework of applied linguistics. The research aims to analyze the syntactic, morphological, and semantic aspects that distinguish the two languages, considering their implications for language learning and translation. Using a qualitative descriptive approach, this study draws on secondary data from linguistic corpora, previous studies, and relevant linguistic theories. The results indicate that Indonesian, as an agglutinative language, relies heavily on affixation to form words, while English tends to use auxiliary verbs and word order to convey grammatical relationships. Syntactically, English follows a strict Subject-Verb-Object (SVO) order, whereas Indonesian allows more flexibility depending on discourse context. Semantic analysis shows that English emphasizes tense and aspect, while Indonesian highlights aspect and context-based meaning. These findings contribute to applied linguistics by providing practical insights for second language acquisition, translation studies, and cross-cultural communication. The study concludes that a deeper understanding of structural differences can enhance language pedagogy and facilitate more effective translation practices.